World Oil Price Shocks in Macroeconomic ASEAN +3 Countries: Measurement of Risk Management and Decision-making a Linear Dynamic Panel Approach - Sanusi, Anuar; Singagerda, Faurani Santi; Sani, Ahmad Zaharuddin (International Journal of Energy Economics and Policy, 2021)
The increase in oil prices in the 1970s has had a quite significant impact over the decades since the rise in inflation has had an impact on hyperinflation, recession, lowered productivity and economic growth. The World Bank (2021) forecasts that oil prices will exceed US$44 per barrel in 2021 and US$50 per barrel in 2022, while several factors affect the World Bank's projections, including the persistence of economic issues in the coming years. The purpose of this paper was to empirically assess the impact of oil prices on ASEAN+3 inflation and economic growth. The framework that can be applied to linear dynamic panel data to achieve this goal is the First Difference-Generalized Moment Method (FD-GMM) estimator method. This study used panel data representing ASEAN+3 countries and annual data over the period 2011-2020. The findings of the study indicated that, over the period, increasing oil prices were associated with higher inflation, and higher economic growth in ASEAN+3. Another result was that higher inflation is related to lower economic growth. Lower and higher economic growth was related to decreased inflation. High inflation creates high costs of economic development and social prosperity, therefore that policymakers are expected to adopt policies that are not only good for the short term, but also good for the long term to establish long-term prosperity and long-term price stability. In addition, a variety of non-economic variables that affect global market price volatility should also be considered to reduce potential market risks. Keywords: oil price shock, inflation, Production Growth, economic development, econometrics JEL Classifications: E31, E42, E63, F43, F62 DOI: https://doi.org/10.32479/ijeep.11249